Supernumerary ovary presenting as a paraduodenal duplication cyst - Yousef El-Gohary; Spyridon Pagkratis; Thomas Lee; Richard J. Scriven (Elsevier, 2015)
Supernumerary ovary is a rare gynecological anomaly and is generally excised due to its potential malignant transformation. We report a case of a patient who was referred for excision of a probable duodenal duplication cyst that was subsequently identified as a paraduodenal supernumerary ovary. Pediatric surgery was consulted on an adolescent patient due to a presumed congenital anomaly of the intestinal tract based on imaging studies.